PEMBAURAN HORISON OPU DAN BELAKE DALAM PROSES REINTERPRETASI UANG DAN TANAH SEBAGAI MAHAR DALAM KONTEKS MASYARAKAT LAMAHOLOT - FX. Wigbertus Labi Halan (Universitas Katolik Parahyangan, 2021)
The purpose of this study is to explain the fusion of opu and belake horizons which resulted in the decision to use money and land as a substitute for ivory in the context of the Lamaholot ethnic community in Waibalun Village. The results of this study found that the point of agreement on the results of this horizon blending occurs because: a), shared knowledge about the status and roles of opu and belake b), mutual awareness regarding the scarcity of ivory, c) material goods that substitute for ivory qualify as a substitute for ivory, d) awareness about the philosophy of baat wekit, e), shared awareness of control of power through the telo-linked marriage system, d), shared awareness of social control in society. This study uses qualitative research methods, with Hans Georg Gadamer's frame of mind